Circular Economy: Technologies for Circulation - Justina Banioniene; Lina Dagiliene (Institute of Economic Research (IER), 2017)
Circular economy in the most recent scientific literature and conducted research is recognized as one of the most advanced models of sustainable economic growth, ensuring competitiveness and opening new businesses with the potential to offer long-lasting economic, environmental and social benefits. Investment in technological innovations may be a way to implement the principle of circular economy at micro (company) level. However, there is a gap in the literature in a systemic research of circular economy technology definition and classification of technologies in the context of creating eco-design products and achieving zero-waste production. Thus this theoretical paper provides a contribution to fill this gap. The aim of this theoretical paper is to define the concept of circular economy technology and to classify these technologies. The methods of systemic, comparative and logical scientific literature analysis, constructive research approach were used in the research. This study provides an extensive review of the scientific literature, with the purpose of grasping the concept of circular economy technology at micro (company) level: origins, definitions, classification, modelling of possibilities to gain, adapt or create circular economy technologies for circular economy implementation. Results evidence that technologies can be classified into basic technologies and technologies to implement circular economy, and the latter could be separated into technologies for eco-design products and for future manufacturing technologies as been detailed in the paper. This research could be useful for preparing government regulation in order to enable the implementation of circular economy, forecasting the need government investment and the institutional efforts to advise and convince companies towards actions implementing circular economy.
Keywords: O3; Q5; 330; circular economy; technology; circular economy technology; classification